Kazakh Variants of the Epic Korugly - Pakizat Auyesbayeva, Togzhan Akimova, Tokhtar Albekov, Karashash Alpysbayeva, Zhumashay Rakysh, (Opción, 2019)
In the article, the questions of the appearance of the epic Korugly on Kazakh territory are investigated. The methodological basis includes theoretical works of national and foreign researchers in the field of Korogly studies and epic studies. As a result, the main character of the epic Korugly is born in a miraculous way. Most of the epic works develop into a voluminous story, being complemented by a poetic form, and represent a whole work. In conclusion, more than ten epic variants have been revealed and about twenty variants as their conclusion that do not duplicate each other